The potential of methanol extract nanoemulsion from gletang flower (Tridax procumbens) as an antibacterial agent against pathogenic bacteria - Sriwijayanti, Sriwijayanti; Pradana, Agrin Febrian; Fauji, Fajar Rizki; Farlina, Iin; Situmeang, Boima (Jurnal Pendidikan Kimia, 2024)
Gletang plant is a weed that grows wild and is widely distributed in various places such as rice fields, plantations, and roadsides. Phytochemical screening of gletang flower extract using methanol revealed the presence of secondary metabolites such as alkaloids, flavonoids, steroids, phenols, terpenoids, and tannins. This study aims to formulate a nanoemulsion from the methanol extract of gletang flowers. The extraction was performed by maceration with methanol 96%. The nanoemulsion was characterized by testing its pH, % transmittance, stability, viscosity and particle size using a particle size analyzer. The antibacterial activity was tested against Staphylococcus aureus and Escherichia coliusing the Kirby-Bauer method. The results of pH characterization, % transmittance, stability and viscosity tests met the standards. The particle size analyzer showed that the particle size ranged between 300-1000 nm. The antibacterial activity tests indicated that all three formulations showed activity against the pathogenic bacteria E. coli, with formulation 3 showing the highest activity.